Mercado de câmbio Brasileiro, intervenç\~oes do Banco Central e controles de capitais de 1999 a 2012 - Estêv\~ao Kopschitz Xavier Bastos; Patrícia Vivas da Silva Fonte (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– In this paper, we describe the operation of the foreign exchange (FX) market in Brazil and discuss the relations between prices of derivatives and spot prices. A literature review of interventions in the FX market is done. Then, we study, in a descriptive way, the interventions of the Central Bank of Brazil, both in the market with physical delivery of currency, and in the swaps market, from 2000 to 2012, as well as the regulations of the Brazilian FX market, from 1999 to 2012, by compiling and briefly analysing the measures taken during the period.
Keywords: E58; F31; G18; 330; exchange; derivatives; currency swap; Central Bank interventions; capital control